“Disillusioned expectations”: The impact of expectations on university belonging among students in Sino-foreign cooperative education institutions - Luo, Peijun; Zhang, Xiaoqiao (Journal of International Students, 2026)
Students’ enrollment expectations significantly shape their university belonging (Yao, 2016). This study investigates the impact of such expectations through qualitative interviews with 13 undergraduate students at a Sino-foreign cooperative education institution in Shanghai. Findings reveal that students’ high expectations centered on: institutional prestige, access to global resources, and the continuation of personal strengths. However, these expectations frequently conflict with academic pressure, institutional fragmentation, and limited resource accessibility. These mismatches can lower students’ overall sense of university belonging. To address this, institutions should clarify potential academic and social challenges during admissions to manage expectations. Closer collaboration in curriculum, activities, and faculty-student engagement is also needed to create an inclusive environment, enhancing university belonging and promoting high-quality international education.